PENERAPAN METODE USER CENTERED DESIGN DALAM MENGANALISIS USER INTERFACE APLIKASI GOTRAVELLY - Aldila Salma Yulita; Eman Setiawan (Jurnal Informatika Teknologi dan Sains, 2022)
Entering the industrial era 4.0, the world focuses on digital technology, one of which is in the tourism sector. It's no wonder that currently there are various kinds of applications for tourism with various advantages and features to make it easier for users. One of the roles of technology in tourism is GoTravelly. GoTravelly is a social media site to review tourist and culinary places from various regions. However, in its use, the GoTravelly application has a low usability level. This is due to problems with the user interface and user experience that are difficult for users to understand. From the existing problems, research was conducted to measure the level of ease of use of the application using the System Usability Scale (SUS) in order to determine the value and level, as well as an implementation using the User Centered Design (UCD) method for designing the GoTravelly prototype. The results of the initial SUS test obtained a score of 60.2, which was included in the low category. The initial SUS score is used as a reference for improving the prototype using the UCD method, so that the SUS score has increased to 91.25 with Grade A and Acceptable.